HYDATID DISEASE OF BONE MASQUERADING AS MALIGNANCY: A CASE REPORT - Safdar, Anam; Tariq, Rabiya; Shahab, Aymen (Khyber Journal of Medical Sciences, 2022)
Hydatid disease continues to be a significant health problem in underdeveloped and developing parts of the world where farming and agriculture is common, but no veterinary control exists. It is also encountered in developed communities where it is common in the immigrants or in people with a history of travel to endemic areas. Hydatid disease of the musculoskeletal system is one of the rarest but extremely debilitating, difficult to diagnose and even more difficult to manage clinical manifestations of the disease. We present a case report of hydatid disease of femur to highlight this rare but important manifestation of this parasitic zoonosis.